Mid-infrared analogue polaritonic reversed Cherenkov radiation in natural anisotropic crystals - Xiangdong Guo; Chenchen Wu; Shu Zhang; Debo Hu; Shunping Zhang; Qiao Jiang; Xiaokang Dai; Yu Duan; Xiaoxia Yang; Zhipei Sun; Shuang Zhang; Hongxing Xu; et al. (Nature Communications, 2023)
Abstract Cherenkov radiation (CR) excited by fast charges can serve as on-chip light sources with a nanoscale footprint and broad frequency range. The reversed CR, which usually occurs in media with the negative refractive index or negative group-velocity dispersion, is highly desired because it can effectively separate the radiated light from fast charges thanks to the obtuse radiation angle. However, reversed CR at the mid-infrared remains challenging due to the significant loss of conventional artificial structures. Here we observe mid-infrared analogue polaritonic reversed CR in a natural van der Waals (vdW) material (i.e., α-MoO3), whose hyperbolic phonon polaritons exhibit negative group velocity. Further, the real-space image results of analogue polaritonic reversed CR indicate that the radiation distributions and angles are closely related to the in-plane isofrequency contours of α-MoO3, which can be further tuned in the heterostructures based on α-MoO3. This work demonstrates that natural vdW heterostructures can be used as a promising platform of reversed CR to design on-chip mid-infrared nano-light sources.